The Protective Role of TLR2 Mediates Impaired Autophagic Flux by Activating the mTOR Pathway During Neospora caninum Infection in Mice - Wang, Jielin; Wang, Xiaocen; Gong, Pengtao; Ren, Fu; Li, Xin; Zhang, Nan; Zhang, Xu; Zhang, Xichen; Li, Jianhua (Frontiers in Cellular and Infection Microbiology, 2021)
Autophagy has been shown to play an essential role in defending against intracellular bacteria, viruses, and parasites. Mounting evidence suggests that autophagy plays different roles in the infection process of different pathogens. Until now, there has been no conclusive evidence regarding whether host autophagy is involved in Neospora caninum infection. In the current study, we first monitored the activation of autophagy by N. caninum, which occurred mainly in the early stages of infection, and examined the role of host autophagy in N. caninum infection. Here, we presented evidence that N. caninum induced an increase in autophagic vesicles with double-membrane structures in macrophages at the early stage of infection. LC3-II expression peaked and decreased as infection continued. However, the expression of P62/SQSTM1, showed significant accumulation within 12 hours of infection, indicating that autophagic flux was blocked. A tandem fluorescence protein mCherry-GFP-LC3 construct was used to corroborate the impaired autophagic flux. Subsequently, we found that N. caninum infection induced the activation of TLR2-AKT-mTOR pathways. Further investigation revealed that TLR2-mTOR, accompanied by the blockade of autophagic flux, was responsible for impaired autophagy but was not associated with AKT. In vitro and in vivo, N. caninum replication was strongly blocked by the kinase inhibitor 3-methyladenine (3-MA, autophagy inhibitor). In contrast, rapamycin (an autophagy inducer) was able to promote intracellular proliferation and reduce the survival rate of N. caninum-infected mice. On the other hand, the accumulation of autophagosomes facilitated the proliferation of N. caninum. Collectively, our findings suggest that the activation of host autophagy facilitates N. caninum replication, and may counteract the innate immune response of the host. In short, inhibition of the early stages of autophagy could potentially be a strategy for neosporosis control.